Evaluation of Higher-Order Skills Development in an Asynchronous Online Poster Session for Final Year Science Undergraduates - Duckworth, Jennifer; Halliwell, Catherine (International Review of Research in Open and Distributed Learning, 2022)
Preparing a scientific poster and presenting it at a conference supports the development of a range of skills in undergraduates that are relevant to further study and the workplace. This investigation focused on an asynchronous online poster session in a final year undergraduate science module at a UK university to assess evidence of higher-order skills development and determine student perceptions of the benefits and challenges of participating in the session. The study analysed 100 randomly selected posters from the 2020 session for evidence of scientific understanding, application, and critical evaluation, together with the feedback received on them. While 73% of the posters demonstrated understanding and 70% application, a lower proportion (42%) demonstrated critical evaluation skills. Seventy-eight percent of posters were considered to have received feedback from peers that gave an effective or partially effective evaluation of scientific content. Focus group discussions involving nine students led to the identification of themes relating to constraints, academic challenges, skills and experience, and personal development. Students recognized the value of the conference for skills development and the experience it gave of “real” science, while acknowledging the challenges involved in producing posters, giving feedback to peers, and managing their time. The asynchronous online poster session enabled students to develop higher-order cognitive and communication skills that are valued by employers. This format provides a pragmatic and easy to implement alternative to synchronous online conferences, which is relevant to the shift toward online learning in higher education, due to the COVID-19 pandemic and increase in distance learning and international students.